Pengaruh Pariwisata, Indeks Pembangunan Manusia, Dana Perimbangan, dan Dana Desa terhadap Kemiskinan di Daerah Istimewa Yogyakarta - Badriah, Lilis Siti; Himawan, Muhammad Deni; Binardjo, Goro (Lingka Ekonomika, 2025)
Poverty remains a major problem in the Special Region of Yogyakarta (DIY) despite the implementation of development programs, including the development of the tourism sector and the allocation of transfer funds from the central government, such as balancing funds and village funds. Human development through increasing the Human Development Index (HDI) is also continuously pursued as part of the poverty alleviation strategy. This study aims to analyze the influence of tourism, HDI, balancing funds, and village funds on poverty levels in five districts/cities in DIY during the 2016–2023 period. The analysis technique used in this study is the panel data regression method with the Fixed Effect Model (FEM) as the best selected model. The results show that tourism and HDI have a significant negative effect on poverty levels, balancing funds have no significant effect on poverty in DIY, and village funds have a significant positive effect on poverty. The implications of this study indicate that the government needs to encourage a more inclusive tourism development model so that its benefits reach a wider community, and prioritize strengthening human development through increasing the HDI for poverty alleviation. Regional governments also need to optimize the use of balancing funds and village funds to be more targeted and support poverty alleviation programs. Improving village fund governance, accountability, and transparency must be a government focus so that the balanced funds and village funds can effectively reduce poverty.